Point-of-need detection of microcystin-LR using a smartphone-controlled electrochemical analyzer - Guan, Tian; Huang, Wenzheng; Xu, Ningxia; Xu, Zhenzhen; Jiang, Lelun; Li, Mengting; Wei, Xiaoqun; Liu, Yingju; Shen, Xing; Li, Xiangmei; Yi, Changqing; Lei, Hongtao (Sensors and actuators. B, Chemical, 2019)
•A portable and wireless point-of-need detection system for microcystin-LR (MC-LR) quantitation was developed and validated.•The detection system consisted of three main parts: screen printed carbon electrodes (SPCEs), smartphone-controlled electrochemical analyzer (SCEA), and Android's smartphone.•A spatiotemporal mapping of MC-LR field detection was conducted to further validate the feasibility of the SCEA for on-site screening. The development of rapid and in situ detection method for microcystin-LR (MC-LR) with portable, reliable, and easy to use devices are highly demanded, but it is still deficient. In this study, a portable and wireless point-of-need detection system for microcystin-LR (MC-LR) quantitation was developed and validated. The whole system consisted of three main parts: screen printed carbon electrodes (SPCEs), smartphone-controlled electrochemical analyzer (SCEA), and Android's smartphone. The SCEA was a homemade ARM STM32 microcontroller-based electrochemical analyzer, which have similar performance compared with a commercially available electrochemical workstation. A smartphone installed with a user-friendly application was employed to control the analyzer, receive and analyze data, and display detection results in real-time. This system can accurately quantitate MC-LR in the range of 0.001–100 μg/L with a detection limit of 0.00011 μg/L, and the results were consistent with LC–MS/MS. In addition, a preliminary MC-LR contamination map was generated using this smartphone-based platform by measuring water samples at 6 reservoirs located in Pearl River Delta (Guangdong Province, China). The cost-effective, reliable and easy-to-use smartphone-based detection system reported here can facilitate active toxicant screening to guarantee the safety of the drinking water, particularly in resource-limited area.